2015
DOI: 10.1007/s00709-015-0757-x
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis of biosynthetic pathway genes vis-à-vis podophyllotoxin content in Podophyllum hexandrum Royle

Abstract: Podophyllum hexandrum Royle is known for its vast medicinal properties, particularly anticancer. It contains higher amount of podophyllotoxin (4.3 %), compared to Podophyllum peltatum (0.025 %) and other plant species; as a result, it has been used worldwide in the preparation of various drugs including anticancer, antimalarial, antiviral, antioxidant, antifungal, and so on. Currently, Etoposide (VP-16-213), Vumon® (Teniposide; VM-26), Etopophos®, Pod-Ben- 25, Condofil, Verrusol, and Warticon are available in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…The lack of Amarogentin in undifferentiated callus cultures and less amount of Mangiferin in callus culture of S. chirayita, might be due to absence of cell machinery programming along with the absence of balanced cell organization to occur in tissue culture condition for metabolite synthesis. As already reported by Kumar et al 2015 wherein callus cultures of S. chirayita accumulates less amount of Amarogentin i.e. 0.05 and 0.09% of Mangiferin and further Kumar et al 2014 reported negligible amount of Mangiferin and very less amount of Amarogentin, when they have already added Adenine sulphate for enhanced production of secondary metabolites, such findings were in relevance to our study, where we have reported 8.57 µg/mg of Mangiferin and negligible amount of Amarogentin at 15 °C in callus initiation stage.…”
Section: Discussionsupporting
confidence: 76%
“…The lack of Amarogentin in undifferentiated callus cultures and less amount of Mangiferin in callus culture of S. chirayita, might be due to absence of cell machinery programming along with the absence of balanced cell organization to occur in tissue culture condition for metabolite synthesis. As already reported by Kumar et al 2015 wherein callus cultures of S. chirayita accumulates less amount of Amarogentin i.e. 0.05 and 0.09% of Mangiferin and further Kumar et al 2014 reported negligible amount of Mangiferin and very less amount of Amarogentin, when they have already added Adenine sulphate for enhanced production of secondary metabolites, such findings were in relevance to our study, where we have reported 8.57 µg/mg of Mangiferin and negligible amount of Amarogentin at 15 °C in callus initiation stage.…”
Section: Discussionsupporting
confidence: 76%
“…Until recently, the knowledge about its biosynthetic pathway was fragmented and key enzymes and corresponding genes were not known (Kumar et al, 2015). A thorough knowledge of complete biosynthetic pathway would ease the access to podophyllotoxin and its natural derivatives which are difficult to produce synthetically (Kamal et al, 2015).…”
Section: Screening For Bioactive Compoundsmentioning
confidence: 99%
“…Currently, a majority of medicinal plants enhance the bioactivity of their medicinal components by inducing and regulating functional genes present in their biosynthetic pathway [25]. Several reports have shown that in plants, there is a significant correlation between the synthesis and accumulation of secondary metabolites and the expression levels found in the functional pathways of their biosynthetic pathways [26,27].…”
Section: Discussionmentioning
confidence: 99%